Creativity Increment and GeoGebra Classroom Quality: Impact on Student Learning - Febrianti, Tri Sedya; Dasari, Dadan (International Journal of Mathematics and Mathematics Education (IJMME), 2024)
Preliminary observation results highlight the importance of utilizing innovative learning media to stimulate students' creativity in both classroom and home-based learning. One interactive learning medium identified for this purpose is GeoGebra Classroom. This research aims to analyze the effect of using the GeoGebra Classroom on the increment of students’ creativity, the effect of the increment of students’ creativity on students’ learning Results, the effect of GeoGebra Classroom quality on students’ learning Results, and the interactivity between students’ creativity and the quality of GeoGebra Classroom learning media. By analyzing pre- and post-implementation learning processes with GeoGebra Classroom, we collected data on increased student creativity. In conclusion, GeoGebra Classroom effectively fosters increased student creativity. And from the process of analyzing the effect of students’ creativity increments, we get the result that the creativity increments give an effect on the learning result of quadratic function materials. Unfortunately, the quality of the learning media GeoGebra Classroom can’t give an effect on the learning result. The insights gained pave the way for future research efforts to delve deeper into the optimization of interactive learning media to improve educational outcomes in a variety of academic contexts.